OTONOMI DESA DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) DI DESA BARUTA LESTARI KECAMATAN SANGIA WAMBULU PROPINSI SULAWESI TENGGARA - Siti Hanura (JI@P, 2015)
This research aimed to study village autonomy related to financialmanagement in the Village of Baruta Lestari Sangia Wambulu Sub-districtButon Regency. Theories related to village autonomy as the manifestation ofgovernmental authority delegation for regulating government tasks toautonomous local goverment in the system of Unified Nation of Republic ofIdonesia were exercised. Qualitative research approach was employed.Participatory observation and unstructured interview data collectingtechniques were employed for collecting the data. Rsearch result indicatedthat (1) Baruta Lestari Village already has fullfill financial managementrelated to Village Income and Expenditure; (2) there is lack of Naturalresources in Baruta Lestari; (3) arrangement of Village Income andExpenditure was decided togatherly by Village Head, Head of House ofVillage Representative (BPD), Village Treasurer, Women Assciation forFamily Welfare (PKK), Head of Village Youth Association (Karang Taruna);Head of Local Community, Informal Community Leaders, and by TraditionalLeaders which are organized as the Institution of Village Consultation (LMD);4) implementation of village financila management was found ineffective; (5)report of financial responsibility is not timelines; and (6) budget realizationhas not already fullfilled village expenditure needs.Keyword: village autonomy; financial management; village autonomy; Village Incomeand Expenditure.